2022
DOI: 10.1111/jam.15429
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial efficacy of plasma-activated water against Listeria and E. coli is modulated by reactor design and water composition

Abstract: Aims: This study aimed to compare the efficacy of plasma-activated water (PAW) generated by two novel plasma reactors against pathogenic foodborne illness organisms. Methods and results:The antimicrobial efficacy of PAW produced by a bubble spark discharge (BSD) reactor and a dielectric barrier discharge-diffuser (DBDD) reactor operating at atmospheric conditions with air, multiple discharge frequencies and Milli-Q and tap water, was investigated with model organisms Listeria innocua and Escherichia coli in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
2
29
1
Order By: Relevance
“…The superoxide anion (•O2 -) has previously been demonstrated to be critical for the antimicrobial activity of the DBDD-PAW (29), and this was confirmed in the current study where the addition of tiron, a •O2scavenger, significantly reduced the antimicrobial activity of the DBDD-PAW. •O2has a short half-life and a negative charge when in a solution with a neutral pH (57) which would typically prevent it from passing through the membrane of bacterial cells (58).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The superoxide anion (•O2 -) has previously been demonstrated to be critical for the antimicrobial activity of the DBDD-PAW (29), and this was confirmed in the current study where the addition of tiron, a •O2scavenger, significantly reduced the antimicrobial activity of the DBDD-PAW. •O2has a short half-life and a negative charge when in a solution with a neutral pH (57) which would typically prevent it from passing through the membrane of bacterial cells (58).…”
Section: Discussionsupporting
confidence: 86%
“…Our previous work had identified . O2as a critical reactive species for the antimicrobial power of the DBDD-PAW (29). We investigated the antimicrobial role of .…”
Section: Inoculation Treatment and Microbial Analysis Of Cucamelonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study also reported that O2 and 1 O 2 were two key reactive species which enhanced the E. coli inactivation effects of PAW substantially (Ma et al, 2020). Rothwell et al (2022) indicated that O2 and/or downstream reactive species to be critical role for bactericidal effects of PAW, particularly in DBD plasma. Therefore, O2 were likely to be one of the key factors for microorganism inactivation in PAW.…”
Section: Resultsmentioning
confidence: 99%